2016
DOI: 10.1007/s00402-016-2529-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomechanical properties: are porcine flexor tendons and bovine extensor tendons eligible surrogates for human tendons in in vitro studies?

Abstract: Porcine flexor and bovine extensor tendons are eligible substitutes with similar stiffness and high failure loads compared with human cadaveric semitendinosus tendons in in vitro studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 33 publications
5
63
0
Order By: Relevance
“…Both porcine flexor tendons and the mechanical setup in this study have been used in other investigations on the strength of suture-tendon constructs [12,[20][21][22][23]. Freezing the samples for storage might have influenced the material properties, but the tensile force gets lower because of freezing [20]. This effect only supports our statement positively.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Both porcine flexor tendons and the mechanical setup in this study have been used in other investigations on the strength of suture-tendon constructs [12,[20][21][22][23]. Freezing the samples for storage might have influenced the material properties, but the tensile force gets lower because of freezing [20]. This effect only supports our statement positively.…”
Section: Discussionsupporting
confidence: 47%
“…However, Domnick et al could demonstrate that for biomechanical investigations, fresh-frozen porcine flexor tendons represent an appropriate substitute for human semitendinosus tendons [20]. Both porcine flexor tendons and the mechanical setup in this study have been used in other investigations on the strength of suture-tendon constructs [12,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…First, porcine flexor profundus tendons were used for the experiment, rather than human tendons. Domnick et al [5] reported that porcine flexor tendons had similar stiffness and type I collagen concentrations compared with human cadaveric semitendinosus tendons, although failure loads were higher, they proposed that porcine flexor tendons are a reasonable surrogate for human semitendinosus tendons. Second, because a single type of suture material was used in this study, no information regarding the potential change in the mechanical behavior of the different grasping suture techniques with different types of suture material can be provided.…”
Section: Discussionmentioning
confidence: 99%
“…The 50-N load was selected to simulate the tension on the sutures tied over a cortical bone bridge in ligament-reconstruction procedures [14], while the 200-N cyclic load was chosen because it locates in the ranges of force on the ACL during level walking (169 N) [5] and the load on the ulnar collateral ligament during throwing (290 N) [4]. A black line was drawn on the tendon at a point 5 cm from the distal end of the tendon, and black marks were made on both suture limbs where they extended from the tendon.…”
Section: Methodsmentioning
confidence: 99%